Management of common femoral artery occlusive disease: A review of endovascular treatment strategies and outcomes. Issue 3 (7th December 2018) - Wong, Gordon; Lahsaei, Saba; Aoun, Joe; Garcia, Lawrence A.
Abstract: Isolated atherosclerotic lesions of the common femoral artery (CFA) are rare but can produce significant claudication and critical limb ischemia. To date, the "gold standard" treatment for this entity has been common femoral endarterectomy (CFE) with or without patch angioplasty. However, surgery does have significant early postoperative complications, with a 15% combined mortality/morbidity. This manuscript sought to perform a comprehensive review of all studies and available data on endovascular treatment of isolated CFA disease and compare its utility to the traditional gold standard treatment. Twenty‐one studies from 1987 to 2018 were included exploring the various CFA endovascular therapies (percutaneous transluminal angioplasty, intravascular stenting, drug‐coated balloons, and directional atherectomy employed to treat CFA disease, in terms of efficacy, safety, and complications). As a conclusion, endovascular interventions provide acceptable short‐term technical outcomes for CFA disease while limiting procedural complications. While only two randomized controlled trials compare short and long‐term outcomes of surgical versus endovascular treatment, further studies are required to clarify the role of endovascular therapy.